Размножение и колебание численности рыжей полевки в условиях Украины - Свириденко, П.А. (Вестник зоологии, 1967)
The article deals with the results of investigations of propagation and variation in number of Clethrionotnys glareolus Schreb. conducted from 1947 to 1954 under natural conditions of «Aleksandria» reservation in Kiev region under conditions of laboratory experiment. It is determined by experiments that the earliest puberty in Clethrionomys glareolus comes at an age of one month, pregnancy lasts for 18 days, duration of life in the experiments varies from 513 to 1164 days, females propagate 4-7 times a year and give 9 —13 broods. It is also determined that mating in Cl. glareolus can occur at the day of delivery; the old animals, survived two or three winters, has various weights (14.8-37.7 g). It testifies to the fact that determination of age in Cl. glareolus populations according to their weigtht can not give reliable results. Under the natural conditions of reservation Cl. glareoulus propagated to 4, 5 times a year. A number of young animals varies from 2 to 10. Feed conditions are the principal factor, determining the intensity of propagation and increasing the number of Cl. glareolus. Dynamic of a number of Cl. glareolus subjected to the sharp season variations: as a rule, after winter a number of Cl. glareolus is minimum, in summer and outumn it sharply increases, in winter it falls again. Shortage of feed and unfavourable weather conditions are the main reasons of Cl. glareolus death in winter.